Medicinal plants in the treatment of respiratoty diseases in childhood: a view from popular knowledge - Karla Rafaella Menezes Araújo; Marta Regina Kerntopf; Dayanne Rakelly de Oliveira; Irwin Rose Alencar de Menezes; Francisco Elizaudo de Brito Júnior (Rev Rene)
This work investigates the popular knowledge regarding the usage of medicinal plants in the treatment of respiratory diseases in childhood. Exploratory descriptive study of qualitative nature, performed in Juazeiro do Norte/CE with twenty-two mothers and/or the ones responsible for the children patients of the Health Family Strategy. The data was collected through semi-structured interviews in the months of June and July, 2011. Collective Subject Discourse to Data analysis technique was used. The research pointed out that the popular knowledge has a great significance and is widely accepted, sometimes being used replacing synthetic drugs. The relevance of the cultural transmission of this knowledge through generations was also pointed out. We believe in the importance of the health professional to discuss the popular practices of health, so they can act more effectively to solve the real problems of health, joining the popular knowledge to scientific knowledge and strengthening such practices.